EUPHEMISM AND DYSPHEMISM IN BLACK PANTHER: A SOCIOPRAGMATIC ANALYSIS OF POWER AND IDENTITY - Santosa Santosa; Masami Permana; Radik Darmawan; Theresia Mundi Astuti; Bayu Andika Prasatyo (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
Language functions as a strategic tool for regulating social interactions and power dynamics through provocation or politeness. This study investigates the use of euphemism and dysphemism in the film Black Panther, focusing on how characters manage sociopolitical tensions. Utilizing Allan and Burridge’s (2009) framework, this qualitative research analyzed 12 linguistic items identified within the film’s screenplay. The data were categorized through a three-stage analytical procedure: classification, description-interpretation, and theoretical synthesis. The results indicate a significant dominance of euphemisms (8 items or 66%) over dysphemisms (4 items or 34%). Euphemisms primarily function as a "linguistic shield," with metaphor being the most frequent strategy, followed by flippancy and figurative expressions. These strategies enable characters to negotiate political responsibilities and preserve national dignity without confrontation. Conversely, dysphemisms are employed as "verbal weapons," notably through synecdoche and non-verbal gestures, to intimidate opponents when diplomatic boundaries are breached. These findings demonstrate that characters prioritize "face-saving" and political stability, reflecting a sophisticated balance between personal loyalty and survival in high-pressure environments.